Mental health nurses: conceptions about professional qualification in a Psychosocial Care Center - Fabíola Lisboa da Silveira Fortes; Maria Angélica de Almeida Peres; Tânia Cristina Franco Santos; Gizele da Conceição Soares Martins; Hercília Regina do Amaral Montenegro; Antonio José de Almeida Filho (Rev Rene)
Objective: analyzing the strategies adopted by mental health nurses for professional qualification in a Psychosocial Care Center. Methods: a historical-social study with written documents and interviews with ten health professionals linked to the Psychosocial Care Center. Data analysis followed chronological order of the facts, and the emerging themes were triangulated and based on concepts that support Brazilian psychiatric reforms. Results:for professional qualifications, nurses invested in participating in congresses, seminars and symposiums; conducting study groups in order to develop new practical skills for mental health some nurses participated more frequently in workshops and followed other professionals for better insertion in this new context. Conclusion: the nurses approached interdisciplinary care to reconfigure their practices, investing in intellectual empowerment and faced the challenge of transforming mental health care in a deinstitutionalized practice.